Contributions of the National Institute of Forestry, Agricultural and Livestock Research to genetic improvement of vegetables - González-Pérez, Enrique; Ramírez-Meraz, Moisés; Canul-Ku, Jaime; Flores-López, Román; Macías-Valdez, Luis Martin (Revista Mexicana de Ciencias Agrícolas, 2021)
Mexico is a center of origin and diversification of horticultural species. Through the genetic diversity that is possessed, several improved materials have been developed, in which, the National Institute of Forestry, Agricultural and Livestock Research has been a very important pillar, being this, one of its main activities. In the genetic improvement program of vegetables, different relevant genotechnical strategies are applied to increase bulb, fruit and tuber yield, such as the selection of clones in garlic, individual selection or hybridization in onion, pedigree or formation of pure lines by self-fecundation in chili; recurrent selection or hybridization in tomato, clonal selection in potato, family selection of maternal half siblings in husk tomato, with which experimental lines, clones, hybrids and varieties have been generated. As a result of those investigations, 19 varieties of garlic, 10 of onion, 21 of chili, 29 of potato and 2 of husk tomato have been released in the 35 years of INIFAP. Varieties that have been adopted by producers in the different agroecological regions of Mexico. However, despite the efforts that plant breeders make to continue with the generation of improved materials, it has not been possible to impact on a market dominated by transnational companies; therefore, necessary to implement INIFAP positioning strategies and invest in conservation and breeding of germplasm that possesses, which in future will result in obtaining better genetic materials that contribute to the benefit of human health.